Mitigation of Voltage Stability Problem Caused in the Hybrid Wind and Solar Outputs - Mohd Fizal, Muhammad Harith Riezman; Soomro, Dur Muhammad (Evolution in Electrical and Electronic Engineering, 2021)
The sun and wind-based power generation are considered to be the alternate sources of green energy where solar energy can be obtained from photovoltaic (PV) panels and wind energy from wind turbines. Due to advancements in renewable energy technology and the continuous rise in petroleum product costs, hybrid renewable energy (RE) systems are becoming more important for producing power to fulfill today’s rising energy demands. This project introduces the hybrid energy system which consists of the combination of solar and wind system connected to the DC load. DC-DC buck boost converter (BBC) with controller unit is also implemented for each source. The aim of this project is to stabilize the output voltages produced by both systems using the power converter for different variations of input parameters (irradiation, temperature and wind speed). The system was simulated in MATLAB/SIMULINK (R2018a). Complete descriptions and detailed results of the simulation show the effective voltage stability of the proposed hybrid system.